2007
DOI: 10.1016/j.bbr.2007.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Two chronic motor training paradigms differentially influence acute instrumental learning in spinally transected rats

Abstract: The effect of two chronic motor training paradigms on the ability of the lumbar spinal cord to perform an acute instrumental learning task was examined in neonatally (postnatal day 5; P5) spinal cord transected (i.e., spinal) rats. At ∼P30, rats began either unipedal hindlimb stand training (Stand-Tr; 20-25 min/day, 5 days/wk), or bipedal hindlimb step training (Step-Tr; 20 min/day; 5 days/wk) for 7 wks. Non-trained spinal rats (Non-Tr) served as controls. After 7 wks all groups were tested on the flexor-biase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 36 publications
1
39
0
7
Order By: Relevance
“…Not surprisingly, training in one task does not necessarily translate into improvements in another task [53][54][55][56]. Even more surprising are findings that training in one task can even have detrimental effects on another task.…”
Section: Activity-based Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Not surprisingly, training in one task does not necessarily translate into improvements in another task [53][54][55][56]. Even more surprising are findings that training in one task can even have detrimental effects on another task.…”
Section: Activity-based Approachesmentioning
confidence: 99%
“…Even more surprising are findings that training in one task can even have detrimental effects on another task. For example, cats with complete SCI transections trained to walk on a treadmill had difficulties in standing in contrast to cats trained to stand, which performed worse in walking than untrained cats [53,56]. Likewise, rats with cervical SCI trained in a reaching task showed deficits in crossing a horizontal ladder [45] or increased activity induced by environmental enrichment promoted recovery in untrained tasks, but interfered with the training in reaching tasks [57].…”
Section: Activity-based Approachesmentioning
confidence: 99%
“…Earlier reports showed also, using different modes of training, that spinal learning is task dependent. 14,15 Furthermore, some data suggest that the spinal cord itself needs to have reached a significant level of excitability for weight-bearing spinal stepping to be expressed. 16,17 It was also shown that the amount of hindlimb loading (using robotic-controlled weight support assistance) as well as the amount of training (number of steps) significantly alter stepping quality promoted by training.…”
Section: Effects Of Tt On Locomotor Recoverymentioning
confidence: 99%
“…O treinamento na esteira é uma forma de atividade física intensamente investigada em estudos experimentais, tanto em humanos (Behrman e Harkema, 2000;Dobkin et al, 2003;Hutchinson et al, 2004;Giangregorio et al, 2005;Dietz, 2009), como em modelos animais (Kunkel-Bagden et al, 1993;De Leon et al, 1998;Edgerton et al, 2001;Ahn et al, 2006;Bigbee et al, 2007;Barriere et al, 2008). Kim et al (2006) afirmam que a recuperação da função motora após uma lesão é mediada por uma reorganização estrutural e funcional do sistema motor residual, que pode ser induzida pelo treinamento motor.…”
Section: De Acordo Com Os Dados Do National Spinal Cord Injury Dataunclassified
“…Como já foi dito no início da introdução, o treinamento na esteira é uma forma de atividade física intensamente investigada em estudos experimentais, tanto em humanos (Behrman e Harkema, 2000;Dobkin et al, 2003;Hutchinson et al, 2004;Giangregorio et al, 2005;Dietz, 2009;Duschau-Wicke et al, 2010), como em modelos animais (Kunkel-Bagden et al, 1993;De Leon et al, 1998;Edgerton et al, 2001;Ahn et al, 2006;Bigbee et al, 2007;Barriere et al, 2008;Heng e De Leon, 2009;Andrade et al, 2010). Já foi demonstrado que tanto em humanos como em ratos lesados medulares, o treinamento na esteira com suporte de peso resulta na melhora da habilidade de andar, e em alguns casos, os padrões de ativação muscular e a cinemática se aproximam daqueles de antes da lesão (Behrman e Harkema, 2000;Nooijen et al, 2009;Heng e De Leon, 2009).…”
Section: Reabilitaçãounclassified